2019
DOI: 10.1136/jech-2019-212825
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and risk of diagnosed dementia after stroke: a cohort study using the Clinical Practice Research Datalink

Abstract: IntroductionThe UK has over 1.2 million stroke survivors. Stroke is a major risk factor for dementia, and along with other risk factors such as hypertension and diabetes, is more common among Black, Asian and other ethnic minorities (BAME). We aimed to explore whether diagnosed dementia differed by ethnicity among adult stroke survivors.MethodologyUsing the UK Clinical Practice Research Datalink and linked hospital data, we conducted a cohort study among patients aged ≥40 years who had an incident stroke betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A further recent study conducted among US Veterans and published after the time period of our search supports our findings [34]. We also showed a similar increase in dementia incidence among those of Black ethnicity in a post-stroke population Shiekh et al [11]. In contrast, Shadlen et al [35] and Evans et al [36] had reported no difference in incidence of dementia comparing Black and White ethnic groups, although these were not included in our review as they had different main exposures of interest.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A further recent study conducted among US Veterans and published after the time period of our search supports our findings [34]. We also showed a similar increase in dementia incidence among those of Black ethnicity in a post-stroke population Shiekh et al [11]. In contrast, Shadlen et al [35] and Evans et al [36] had reported no difference in incidence of dementia comparing Black and White ethnic groups, although these were not included in our review as they had different main exposures of interest.…”
Section: Discussionsupporting
confidence: 90%
“…A cohort study using routine healthcare data from the UK looked at ethnic differences in dementia incidence and reported higher incidence dementia in Black men and women compared to White men and women [ 8 ]. A cohort study using routine healthcare data from the UK looked at ethnic differences in incidence of diagnosed dementia after stroke and reported higher incidence in the Black ethnic group compared to the White ethnic group [ 11 ]. However, it is unclear whether these differences are also observed globally, and the relative contribution of biological and socio-cultural factors is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, empirical estimates indicate that the prevalence of AD in Black people is highly variable, ranging from 14% to 500% higher than that of white people [ 129 , 130 , 131 ]. It is believed that several factors contribute to this discrepancy in the risk of AD among AAs, including genetics, lifestyle factors, socioeconomics, and other comorbidities (e.g., hypertension, diabetes mellitus, stroke, myocardial infarction, and congestive heart failure) [ 132 , 133 , 134 ]. Other sociological factors, including healthcare access/insurance coverage, systemic racism, clinical presentation, and the timing of diagnosis, further exacerbate these disparities in dementia care [ 135 , 136 , 137 , 138 ].…”
Section: Risk Factors/susceptibility Of Ad In African Americansmentioning
confidence: 99%
“…1 The observation is also that, compared with other raceethnicities in Europe and North America, people of African origin are more severely impacted by stroke and its neurocognitive complications. 2,3 In line, vascular risk factors such as diabetes and hypertension as well as socio-economic indicators of stroke and dementia have been shown to be significantly higher in sub-Saharan Africa (SSA) than other world regions. 4 This is in tandem with a fast-rising incidence of stroke in SSA.…”
Section: Introductionmentioning
confidence: 99%